Power, poverty and peacebuilding: the violence that sustains inequalities and undermines peace in Colombia. Issue 6 (1st November 2020) - Gordon, Eleanor; Henao, Sebastian Restrepo; Duque, Alejandra Zuluaga; Dolan-Evans, Elliot
ABSTRACT: Despite the promise of the 2016 Colombian peace agreement, this paper argues that the intersection of poverty, insecurity and exclusion threatens sustainable peace in Colombia. In asserting this argument, the paper advances two case studies: the false positives scandal, which demonstrates the vulnerability of the poor to various security threats, and the coca eradication programme, which has fuelled further violence and economic insecurity on impoverished rural people. This paper uses these cases to highlight how poverty is used to legitimise, and is intertwined with, structural and physical violence in Colombia. These cases further shed light on the political economy of violence in Colombia, which legitimises the unequal distribution of wealth, exposes the poor to violence, and disguises crimes of the powerful through the narrative of the deviant or underserving poor and the rhetoric of maintaining security or advancing development. Fundamentally, this article posits that although the post-conflict moment presents a profound opportunity for transformational change, continued socio-economic inequalities and violence against the poor in Colombia will affect the ability to create a sustainable and meaningful peace.